200k views
0 votes
1.(02.01)
Solve -4(x + 1) – 3 = -3(x – 4). (1 point)
O
-19
19
2.

2 Answers

3 votes

Answer:


\boxed {x = -19}

Explanation:

Solve for the value of
x:


-4(x + 1) - 3 = -3(x - 4)

-Use Distributive Property to both sides of the equation:


-4(x + 1) - 3 = -3(x - 4)


-4x - 4 - 3 = -3x + 12

-Combine like terms:


-4x - 4 - 3 = -3x + 12


-4x - 7 = -3x + 12

-Take
-3x and add it to
-4x:


-4x - 7 + 3x = -3x + 3x + 12


-x - 7 = 12

-Add both sides by
7:


-x - 7 + 7 = 12 + 7


-x = 19

-To make the variable
x positive, divide both sides by
-1:


(-x)/(-1) = (19)/(-1)


\boxed {x = -19}

Therefore, the value of
x is
-19.

User Betaman
by
5.8k points
1 vote

Answer:

x = -19

Explanation:

hope this help :)

User Luke Bajada
by
6.9k points